Application of narrow‐spectrum illumination and image processing to measure surface char formation in lateral ignition and flame spread tests. (5th March 2019) - Gatien, Seth; Young, Tim; Hoehler, Matthew S.; Gales, John
Summary: The Lateral Ignition and Flame Spread Test (LIFT) is used to characterize fire ignition and flame spread on solid materials. This test requires the operator to visually monitor the flame spread over a combustible material and manually record the position of the flame during an experiment. Visual inspection limits the quantity of data obtained from a test and introduces uncertainty in the measurement. In this study, we use narrow‐spectrum light with a peak wavelength of 450 nm and a digital camera with frequency‐matched optical filters to capture images of surface charring, which underlies the flaming combustion, in a LIFT apparatus. The imaging technique reduced unwanted energy emissions from the flame in the visible light spectrum, allowing the test operator to directly view the charring of the material, which is otherwise hidden behind the flames. We describe data processing routines to analyze the sequences of high‐resolution images. The method improves temporal and spatial resolution of the surface charring compared with visual observations.